2019
DOI: 10.3389/fimmu.2019.01915
|View full text |Cite
|
Sign up to set email alerts
|

Hyperactive Follicular Helper T Cells Contribute to Dysregulated Humoral Immunity in Patients With Liver Cirrhosis

Abstract: Objectives: Liver cirrhosis (LC) is usually accompanied by cirrhosis associated immune dysfunction (CAID), including reduced naïve T cells and memory B cells. However, little is known regarding on follicular helper T (Tfh) cell compartments in cirrhotic patients, especially in the secondary lymphoid organs such as spleen. This study characterizes splenic Tfh cells and explores its association with humoral immunity and disease progression in cirrhotic patients. Methods: Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 34 publications
4
14
2
Order By: Relevance
“…1d–f ). In accordance with our previous study 26 , plasmablasts were found to be elevated in the spleens of cirrhotic patients. IgA memory B cells were found to be significantly decreased in peripheral blood; however, their counterpart in the spleen seemed to have largely remained at a level comparable to that of the healthy subjects (Fig.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…1d–f ). In accordance with our previous study 26 , plasmablasts were found to be elevated in the spleens of cirrhotic patients. IgA memory B cells were found to be significantly decreased in peripheral blood; however, their counterpart in the spleen seemed to have largely remained at a level comparable to that of the healthy subjects (Fig.…”
Section: Resultssupporting
confidence: 93%
“…A previous study showed that IgM + CD27 + B cells have a higher capacity to migrate toward CXCL13 49 , suggesting an ability of these cells to enter B cell follicles. Indeed, we observed a higher expression of CXCL13 in cirrhotic patients, and the increased splenic Tfh cells may facilitate the differentiation of plasma cells 26 . These data suggested that the increased engagement of MZB cells in GC reactions likely exhausts the splenic MZB cell pools during liver cirrhosis.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Additionally, patients with cirrhosis may have impaired cell-mediated and humoral immunity and so the presence of anti-HEV IgM may not be a reliable marker for active infection in this patient population. 24 , 25 HEV RNA may have been a more reliable marker of infection in these patients. Although the increased risk of poor prognosis in cirrhotics who become superinfected with HEV seems well supported, that is not surprising since the same risks have been shown with other viral superinfections, such as with hepatitis A virus (HAV) and hepatitis D virus (HDV).…”
Section: Effects Of Dual Infection On Severity Of Liver Diseasementioning
confidence: 99%